Broad spectral-response organic D–A–π–A sensitizer with pyridine-diketopyrrolopyrrole unit for dye-sensitized solar cells. Issue 16 (2nd February 2016) - Guo, Fuling; Liu, Xuepeng; Ding, Yong; Kong, Fantai; Chen, Wangchao; Zhou, Li; Dai, Songyuan
Abstract : In this work, four D–A–π–A sensitizersPDPP-I–IV based on pyridine-flanked DPP moieties (PDPP) were designed and synthesized for broadly spectral-response in dye-sensitized solar cells. Abstract : In this work, four D–A–π–A sensitizersPDPP-I–IV based on pyridine-flanked DPP moieties (PDPP) were designed and synthesized for dye-sensitized solar cells. Remarkably, the incorporated electron-withdrawing unit of pyridine-flanked DPP improves the light-harvesting ability and modifies the electrochemical and absorption properties, generating a broader IPCE wavelength responding region. The electrochemical experiments and time-resolved photoluminescence measurements indicate the ability of electron-injection into the TiO2 conductive band from the excited sensitizer. The transient absorption spectra were measured to investigate the feasibility of the dynamics for oxidized-state sensitizer regeneration. The IPCE spectra demonstrate the broad spectral response region of these sensitizers. Especially, the IPCE ofPDPP-III reached the near infrared (NIR) region (>800 nm) with the highest short-circuit current of 16.17 mA cm −2 in these sensitizers. Furthermore, the electrochemical impedance spectroscopy (EIS) experiments suggest that the electron-lifetime and charge recombination resistance increased when attaching the stereo substituted groups ( R 2 ) on the PDPP moiety, resulting in a higher open-circuit voltage ( V oc ). It can be found thatPDPP-II based DSSCs with liquid electrolyte exhibited the highest V oc (523 mV) and power conversion efficiency (PCE) of 5.26%.